Semantic Equivalence in the Translation of Mechanical Engineering Terms in Bilingual Abstracts of JurnalTeknik Mesin - Farahsani, Yashinta; Setiawati, Sri Ani Puji (Universitas Brawijaya, 2026)
The use of bilingual abstracts in Indonesian academic journals plays an important role in increasing the international visibility of scientific publications. However, inaccuracies in translating technical terminology may lead to semantic shifts and reduce the clarity of scientific communication. This study investigates semantic equivalence in the translation of mechanical engineering terms found in bilingual abstracts of Jurnal Teknik Mesin. The objectives of this study are to analyze the degree of semantic equivalence achieved in the translation process and to identify the dominant equivalence types used in translating mechanical engineering terminology from English into Indonesian. This research employed a qualitative descriptive method. The data consisted of 85 mechanical engineering terms collected from 20 bilingual abstracts published in Jurnal Teknik Mesin between 2021 and 2024. The data were selected based on the occurrence of specialized mechanical engineering terminology and analyzed using the semantic equivalence framework proposed by Nida and Taber (1982), supported by Newmark’s (1988) theory of technical translation. The findings reveal that formal equivalence is the dominant translation type, accounting for 52% of the data, followed by dynamic equivalence (28%), partial equivalence (13%), and semantic shift (7%). Formal equivalence is mainly used for standardized technical terms such as tensile strength and heat transfer, while semantic shifts frequently occur due to inaccurate lexical selection and insufficient technical understanding. The study concludes that maintaining semantic equivalence in bilingual engineering abstracts requires both linguistic competence and domain-specific knowledge to ensure precision, consistency, and clarity in technical communication.